Effect of Maternal Positioning with Occipito-posterior Fetal Position during Labor on Pain Intensity and Satisfaction of Mothers - Kobra Bahmaei; Mina Iravani; Parvaneh Moosavi; Mohammad Hosein Haghighizadeh (Mashhad University of Medical Sciences, 2018)
Introduction: The occipito-posterior fetal positions are the most common type of malposition of the occiput. Increasing maternal pain and need for epidural anesthesia are among the complications of this condition. Maternal position during labor can influence her pain intensity. This study aimed to investigate the effect of maternal position in the active phase of labor on the pain intensity and satisfaction. Method: This randomized controlled trial was conducted among 180 primiparous pregnant women with a singleton pregnancy and occipito-posterior fetal position referred to a maternity hospital in Ramhormoz, Iran, 2017. The samples were selected based on the purpose using a random number generating software. They were randomly assigned into three groups of semiprone position (n=45), knee-chest position (n=45), and control group (n=90). The control group gave birth in the supine position. From half an hour after randomization until delivery, all the participants were alternately (15 to 30 minutes per hour) located in defined positions. Data were collected using a visual analog scale for pain, observation, and examination of the record form. Data analysis was performed using Chi-squared and analysis of variance tests in SPSS software, version 24. The significance level was considered as P≤0.05. Results: According to the results, the intensity of pain in the intervention groups was significantly lower than the control group. Additionally, the satisfaction level of mothers in the intervention group was higher than the control group (P<0.0001). Conclusion: It seems that semiprone and knee-chest positions in mothers with occipito-posterior fetal position during the active phase and the second stage of labor were useful for relieving labor pain and increasing the satisfaction of mothers.